Cultural malpractice during pregnancy, childbirth, and the postnatal period and its associated factors among women who gave birth once in Dire Dawa city administration, Eastern Ethiopia, in 2021 - Mickiale Hailu; Aminu Mohammed; Yitagesu Sintayehu; Daniel Tadesse; Legesse Abera; Neil Abdurashid; Milkiyas Solomon; Momina Ali; Dawit Mellese; Tadesse Weldeamaniel; Teshale Mengesha; Tekelebirhan Hailemariyam; et al. (Frontiers Media S.A., 2023)
BackgroundCultural practices are any experiences or beliefs that are socially shared views and behaviors practiced in a certain society at a certain time. Cultural malpractices are defined as socially shared views and traditionally accepted behaviors experienced in a certain society that harm maternal health. Worldwide, the period of pregnancy, labor, and delivery is embedded with different beliefs, customs, and rituals in different societies that contribute a lot to maternal death. They are responsible for the annual deaths of 303,000 mothers and 2.7 million newborns globally. In developing countries, it accounts for approximately 5%-15% of maternal deaths. In Ethiopia, approximately 18% of infant deaths occur due to cultural malpractice, and 52% of pregnant mothers give birth at home following cultural customs in Dire Dawa city. The objective of this study was to assess cultural malpractices during pregnancy, childbirth, and the postnatal period and its associated factors among women who gave birth once in Dire Dawa City in 2021.MethodsCommunity-based mixed study was conducted. A total of 624 study participants were selected through a systematic random sampling technique, and a purposive sampling method was used for qualitative data. The study was conducted in the randomly selected Kebeles of Dire Dawa City, Eastern Ethiopia, from November 1 to December 30, 2021. Data were entered into Epi Data version 4.1 and exported to SPSS version 24 for analysis. Bivariate and multivariate analyses were done, and the degree of association was measured by using the odds ratio with 95% CI and significance was declared at a p-value of <0.05. The qualitative data were analyzed thematically using ATLAS-ti version 7.ResultsThe overall prevalence of cultural malpractice during pregnancy, childbirth, and the postnatal period was 74.6% [95% CI: 70.59%, 77.49%]. Women over the age of 35 were two times more likely [AOR 2.61, 95% CI, 1.45-4.72] to commit cultural malpractice than women aged 15-24 and 25-34. Those with no antenatal care (ANC) follow-up were three times more likely to commit cultural malpractice [AOR 3.57, 95% CI, 1.72-7.40], those who were absent from health education were nearly two times more likely to commit cultural malpractice [AOR 1.83, 95%CI, 1.25-2.67], and women whose culture allows harmful traditional practices were nearly two times more likely to commit cultural malpractices than their counterparts [AOR 1.69, 95%CI, 1.29-2.54].ConclusionIn this study, nearly three-fourths of participants were involved in cultural malpractices. Therefore, strengthening community education and behavioral change messages on the importance of ANC and avoiding unhealthy care during pregnancy, childbirth, postnatal and neonatal periods, especially with pregnancy at old age (age > 35), may help to reduce cultural malpractices.